Morphology, Biomass, and Forage Quality of Sorghum bicolor cv. Bioguma-2 Treated with Soil Ameliorants on Post-Coal Mining Land - Kuswoyo, A.; Abdullah, L.; Karti, P. D. M. H.; Human, S.; Rostini, T.; Mulyono, E. E.; Wawan, E. (Tropical Animal Science Journal, 2025)
Reclamation of post-coal mining land is a valuable opportunity for transforming the land into agricultural cultivation of forage crops for livestock feed production. We conducted an experiment in the Asamasam coal mining spot, Tanah Laut Regency, South Kalimantan, to investigate the effect of some soil ameliorant materials, and Sorghum bicolor cv. Bioguma-2 (Bioguma-2 sorghum) on morphological characteristics and biomass production. Seven soil ameliorant treatments were tested: control (P0), single applications of humic acid (P1, 28 L ha⁻¹), dolomite (P2, 5.8 t ha⁻¹), and organic compost (P3, 15 t ha⁻¹), and treatment combinations of humic acid + compost (P4), dolomite + compost (P5), and humic acid + dolomite + compost (P6) with the same doses of P1, P2, and P3. The data were subjected to analysis of variance, and any significances between treatments were analyzed by Duncan’s Multiple Range Test. The results indicated that the combined ameliorant materials improved morphological characteristics and biomass production. Treatment P6 showed the highest effectiveness on soil quality, plant survival rate, most morphological traits, and all yield parameters, followed by other treatments with comparatively lower performance. P6 produced the highest crude protein content across treatments. The combination of multi-ameliorants (humic acid, dolomite, and organic compost) is more effective than single ameliorants in improving soil quality, plant survival, morphological traits, and biomass yield of Sorghum bicolor cv. Bioguma-2 on post-coal mining land. These results indicate that using combined soil ameliorants is a promising strategy to enhance forage crop production on degraded mining soils. However, natural declines in plant performance during later harvest stages suggest the need for further nutrient management to sustain productivity over time.